COMPARATIVE EDUCATION: NOTES FROM THE PERSPECTIVE OF POSTGRADUATE STUDENTS IN EDUCATION - Campos Martins, Chelsea Maria de [UNESP]; Amaral, Gabriel Pereira do [UNESP]; Santos, Rosimeire dos (Unesp-faculdade Ciencias & Letras, 2021)
This study presents an analysis of Comparative Education from the basic material presented in the discipline Introduction to Comparative and International Education Studies of the PostGraduate Program in Education, at UNESP, campus of Marilia/SP, mainly focused on research and methodological procedures. Then, a synthesis of selected research on the subject presented by graduate students is presented. Through content analysis, the study revealed that Comparative Education, as an interdisciplinary research bias, requires schemes that are supported by studies that address social, political and cultural aspects, passing through reflective criticism, understanding the specifics of education, as well as by trends, internal and external influences, and the challenges of Comparative Education in the educational conjecture of Brazil and the world. The analysis allows us to infer that studies focused on this methodology do not seek only to find similarities or differences, but to promote in-depth discussions about the role of Comparative Education for educational development and its influence on the history of education, permeating challenges, possibilities and contributions.
Keywords: Comparative education; Research in comparative study; Postgraduate stricto sensu